2020
DOI: 10.2495/sdp-v15-n1-57-68
|View full text |Cite
|
Sign up to set email alerts
|

The South African quick service restaurant industry and the wasteful company it keeps

Abstract: Despite a tough South African (SA) economic climate, consumers are demanding broader menus, wider selections and faster food. With the sudden surge in the SA quick service industry, efficient supply chain management is pivotal for a sustainable food system. recent estimates suggest that between one third to half of all food produced never reach the human stomach. In SA alone, annual food waste is estimated at r61.5 billion (current exchange rate r14.39 = $1). With an average of 11 million people (almost a quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In sum, interviewees confirmed that certain factors, such as seasonality, lack of profitability, lack of time, and cost, contributed to inadequate hiring decisions and lack of training [71], with the consequence of increased food losses and waste caused by staff behavior.…”
Section: Staff Hiring Process and Trainingmentioning
confidence: 88%
“…In sum, interviewees confirmed that certain factors, such as seasonality, lack of profitability, lack of time, and cost, contributed to inadequate hiring decisions and lack of training [71], with the consequence of increased food losses and waste caused by staff behavior.…”
Section: Staff Hiring Process and Trainingmentioning
confidence: 88%
“…Similarly, the country's fast-food industry is burgeoning in both urban and rural locations [39]. Outlets are visited at least once a month by most consumers, and broiler meat, following global trends, plays a dominant role in the products on offer [39][40][41].…”
Section: Plos Onementioning
confidence: 99%
“…The tourism sector in South Africa contributed 2.8% to the gross domestic product (GDP) which is equivalent to R139 billion and this was expected to grow to R145.3 billion by 2019 Statistics South Africa (2019). The South African fast service restaurant industry which is a sub-sector of the food and beverages industry is growing tremendously and was valued at R300 billion in 2015 and the number of consumers was expected to be around 42 million by 2017/2018(Marx-Pienaar et al, 2020. Fast Service Restaurants (QSR) allow for lower traditional services with reduced prices while ensuring speedy service and efficiency (Seo, 2020).…”
Section: Overview Of the Fast Service Industry In South Africamentioning
confidence: 99%
“…A notable change in eating habits have been seen over the past 40 years with more people consuming food prepared out of the home (Seguin et al, 2016). Most customers will visit a fast service restaurant at least once a week and, with lives getting busier, there is a growing fondness for cheap food with no waiting time (Marx-Pienaar et al, 2020). As a result of the need for cheap and quick food, Koh et al (2014) highlight that fast service restaurants usually face the problem of long queues due to their affordability.…”
Section: Jmer 2022 03(1) 26─45mentioning
confidence: 99%
See 1 more Smart Citation